Clinical utility of smartphone-based audiometry for early hearing loss detection in HIV-positive children: A feasibility study - Mukovhe Phanguphangu; Andrew J. Ross (AOSIS, 2021)
Background: Paediatric human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) often manifests with hearing loss (HL). Given the impact of HL, early detection is critical to prevent its associated effects. Yet, the majority of children living with HIV/AIDS (CLWHA) cannot access hearing healthcare services because of the scarcity of audiologists and expensive costs of purchasing screening equipment. Alternative solutions for early detection of HL are therefore necessary. Aim: The overall aim of this study was to assess the feasibility of using self-administered smartphone-based audiometry for early HL detection amongst CLWHA. Setting: This study was conducted at the paediatrics department of a state hospital in the Eastern Cape province, South Africa. Methods: This was a feasibility study conducted amongst twenty-seven (27) CLWHA who were in the age group of 6-12 years. The participants self-administered hearing screening tests using a smartphone-based audiometric test. The primary end-points of this study were to determine the sensitivity, specificity and test-retest reliability of self-administered hearing screening. Results: The sensitivity and specificity for self-administered screening were 82% and 94%, respectively, with positive and negative predictive values of 90% and 88%, respectively. Moreover, a strong positive test-retest reliability (r = 0.97) was obtained when participants self-administered the screening test. Conclusion: Six- to 12-year-old CLWHA were able to accurately self-administer hearing screening tests using smartphone-based audiometry. These findings show that self-administered smartphone audiometry can be used for serial hearing monitoring in at-risk paediatric patients.